2014
DOI: 10.1186/s13018-014-0118-z
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and properties of acellular porcine anulus fibrosus for tissue engineering in spine surgery

Abstract: BackgroundOver the last few years, new treatments for a damaged intervertebral disc (IVD) have included strategies to repair, replace, or regenerate the degenerative disc. However, these techniques are likely to have limited success, due to insufficiently effective means to address the damaged anulus fibrosus (AF). Here, we try to develop a bioprocess method for decellularization of the xenogeneic AF tissue, with a view to developing a scaffold as a potential candidate for clinical application in spinal surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…There was also no significant difference in collagen content between native and decellularized AF. Our present data showed that 5.6% of GAG was lost during processing, which was an improvement over our previous protocol, which resulted in a 15.9% loss of GAG (Wu et al 2014 ).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…There was also no significant difference in collagen content between native and decellularized AF. Our present data showed that 5.6% of GAG was lost during processing, which was an improvement over our previous protocol, which resulted in a 15.9% loss of GAG (Wu et al 2014 ).…”
Section: Discussionsupporting
confidence: 55%
“…One tissue engineering strategy for developing biomaterials is to decellularize xenogeneic tissues by removing immunogenic cells. This method has been successfully used to develop biomaterials for use in cartilage, the meniscus, ligaments, and tendons, with impressive results (Gilbert et al 2006 , 2009 ; Stone et al 2007 ; Wu et al 2014 ; Xu et al 2014 ). Xenogeneic and allogeneic cellular antigens are recognized as foreign by the host, thereby inducing an inflammatory response or an immune-mediated rejection of the tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has previously developed gentle decellularization techniques for nerve tissue to preserve essential proteins, proteoglycans, and microstructure [39,43], which would be ideal for the delicate nucleus pulposus. To date, some research has been performed to create decellularization protocols for the nucleus pulposus [44][45][46][47], anulus fibrosus [48,49], and the intact IVD [50]. These matrices have shown promise as viable scaffolds for IVD cells as well as drivers of stem cell fate [44][45][46][47][48][49][50], although they are not injectable or in situ gelling.…”
Section: Introductionmentioning
confidence: 99%
“…The AF can be divided into inner and outer layers, the outer layer being mainly composed of type I collagen, whereas the inner AF is mainly type II collagen. From outer to inner AF, the content of water and proteoglycans increases, whereas the content of type I collagen gradually decreases . The NP, which is located in the central region of the IVD and has a jelly‐like structure, is rich in proteoglycan, type II collagen and water .…”
Section: Methodsmentioning
confidence: 99%